Protests and Policies: How Radical Social Movement Activists Engage with Climate Policy Dilemmas. (February 2021) - Corry, Olaf; Reiner, David
How do radical movements seeking fundamental social change engage with nearer-term policy dilemmas? Disciplinary boundaries and practical obstacles have limited research into protester policy engagement. Using a hybrid method combining participant-observation and expert-led focus groups, we document activist attitudes concerning controversial climate policy options. Data gathered at 'Climate Camps' in six national contexts are presented alongside evidence from similar 'participant-instigator' events at Green Party conferences. We find activists engaged in direct action outside the established political system had policy knowledge and agendas comparable to or surpassing those active within the system. Support for radical change appears correlated with – rather than opposed to – knowledge and interest in policy agendas. As climate protests escalate it is important to understand 'protester policy engagement' – the processing, production and communication of changes proposed from a position outside the established political system and to theorise this with, rather than in contradistinction to, social movement identity.